Did sanctions help Putin? - Aleksandra Peeva (Freie Universität Berlin, School of Business & Economics, 2019)
Do sanctions strengthen the targeted regime? I analyze the 2014 imposition of Western sanctions on Russia and its impact on voting. The US and the EU introduced targeted measures against Russian entities and individuals related to Putin's regime. Using polling station-level data I investigate whether Putin gained relatively more support among those local constituencies which were geographically close to a sanctioned firm. I find a significant effect of targeted sanction imposition on the vote share in presidential elections between 2012 and 2018. Putin gained 1.54 percentage points at those polling stations that had a sanctioned firm in immediate vicinity. Targeted sanctions imposition also affected voter turnout. The effect on voting can be explained as rally-around-the-flag in the face of sanctions, as long as voters did not endure economic losses through a decline in some sanctioned firms' economic performance.
urn:nbn:de:kobv:188-refubium-24769-4
Keywords: D72; P26; 330; sanctions; rally-around-the-flag; voting; Russia